2014
DOI: 10.1002/ece3.1041
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between DRD4 polymorphisms and phenotypic correlations of behaviors in the collared flycatcher

Abstract: There is increasing evidence that the genetic architecture of exploration behavior includes the dopamine receptor D4 gene (DRD4). Such a link implies that the within-individual consistency in the same behavior has a genetic basis. Behavioral consistency is also prevalent in the form of between-individual correlation of functionally different behaviors; thus, the relationship between DRD4 polymorphism and exploration may also be manifested for other behaviors. Here, in a Hungarian population of the collared fly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 78 publications
5
42
0
2
Order By: Relevance
“…These findings provide further evidence for the genetic relationship between DRD4 and explorative and risk-taking behaviours, as shown in previous studies (e.g. Fidler et al 2007;Garamszegi et al 2014;Mueller et al 2014). For example, Garamszegi et al (2014) showed that male pied flycatchers that were homozygous for a specific SNP in DRD4 took more risk (shorter FIDs) than heterozygous males.…”
Section: Association Between Snps or Indels And Behavioural Traitssupporting
confidence: 87%
See 1 more Smart Citation
“…These findings provide further evidence for the genetic relationship between DRD4 and explorative and risk-taking behaviours, as shown in previous studies (e.g. Fidler et al 2007;Garamszegi et al 2014;Mueller et al 2014). For example, Garamszegi et al (2014) showed that male pied flycatchers that were homozygous for a specific SNP in DRD4 took more risk (shorter FIDs) than heterozygous males.…”
Section: Association Between Snps or Indels And Behavioural Traitssupporting
confidence: 87%
“…Fidler et al 2007;Garamszegi et al 2014;Mueller et al 2014). For example, Garamszegi et al (2014) showed that male pied flycatchers that were homozygous for a specific SNP in DRD4 took more risk (shorter FIDs) than heterozygous males. This result is in line with our finding for females, but not for males.…”
Section: Association Between Snps or Indels And Behavioural Traitsmentioning
confidence: 99%
“…These results are in accordance with previous studies (e.g. Garamszegi et al 2014;Møller 2014;van Dongen et al 2015b) and suggest that variability in FID is much greater between species than it is within species. This justifies the use of a small number of FIDs per individual and multiple FIDs from contrasting sites or habitats (see below).…”
Section: Reporting Flight-initiation Distancessupporting
confidence: 83%
“…DRD4-KO mice are less prone to explore new environments (Dulawa, Grandy, Low, Paulus, & Geyer, 1999), while DEAF1-KO mice exhibit stronger anxiety (Vulto-Van Silfhout et al, 2014). Evidence for a role of DRD4 in behaviour and dispersal is also found in several bird species (Fidler et al, 2007;Garamszegi et al, 2014) and is linked to adaptation to changing climate in a migratory songbird (Bay et al, 2018). In humans, this gene has been the focus of several behavioural studies, showing that polymorphism at this gene predicted individual differences in novelty-seeking (Ebstein et al, 1996) and impulsivity (Carpenter, Garcia, & Lum, 2011).…”
Section: Neurexin-1 Cntnap2mentioning
confidence: 97%